The Vernacularization of Quran Interpretation in Bugis Land - Mursalim, Mursalim; Fansuri, Fuad; Husain, Muhammad Zakir Bin; Amir, Abdul Muiz (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2024)
The vernacularization of the Qur'an has become an important study area for Indonesian scholars. However, translations or interpretations in the local languages of eastern Indonesia, especially South Sulawesi, have received limited attention. This research aims to fill this gap by examining the development of Qur'anic interpretation in the Bugis language in South Sulawesi. Employing a descriptive-analytic method and a social-historical approach, the study reveals that all authors of Bugis-language interpretations originate from the Madrasah Arabiyah Islamiyah (MAI), established by Anregurutta (AG) H. As'ad. As a result, these authors demonstrate comparable perspectives, styles, methods, and ideologies, distinguishing the vernacularization efforts in South Sulawesi from those in other parts of Indonesia. The research highlights the crucial role of the As'adiyah Islamic Boarding School in fostering the Bugis tafsir tradition in eastern Indonesia. Additionally, it finds that the motivations for translating or interpreting the Qur'an into Bugis encompass the goals of deepening comprehension of Islamic teachings within the indigenous community and preserving the Bugis language and culture within the context of Islamic discourse. Ultimately, the study illustrates the harmony between Islamic teachings and the socio-cultural context in Indonesia by examining the efforts to adapt Islamic practices to the local setting in Bugis Land